Pola Sintaktis Lakon Jaka Sukara - Munawarah, Sri (Paradigma: Jurnal Kajian Budaya, 2013)
The history of Malay language has been going through a long way. Kridalaksana (1991:5) divided the development period of Malay language into four: the Melayu Kuna era (the 7th-14th century CE), the Melayu Klasik/Tengahan era (the 14th-18th), the Melayu Peralihan era (the 19th), and the Melayu Baru era (the 20th century). The Betawi language is the only Malay language that existed in Java Island. Dullaurier, as quoted by Hollander (1983;1984), said that the Malay language is divided into two groups: Malay language Malaka accent and Betawi accent (Muhadjir, 1999:21). In this research, the script of Lakon Jaka Sukara became the data source to find the characteristic features of Malay Betawi language syntax that is written in the script. Lakon Jaka Sukara is one of the scripts assumed to have been written by the Betawi people. In this case, the script of Lakon Jaka Sukara will be analyzed in its syntactic pattern. The research of the Betawi language writing variety, especially the ancient script has rarely been done. That case became important for this research to be conducted. After seeing the whole script, there is syntactic patterns that became the characteristic features of the writing variety of the Betawi language. That syntactic pattern is that there is construction property or possessive phrase, collocation [kasi], [beri], or [kerja] that is followed by verbs, construction [apa] that is followed by nouns, construction [barang] that is followed by [di mana], construction [pun] that is in front of male pronouns, and construction [pun] that is on the back of female pronouns.